The concept of the development of methodological work at the Institute of Social Sciences and International Relations of the FSAOU in SevSU - Danilchenko S. L. (Pedagogy and psychology: development prospects, 2022)
The main task of methodological work at the university is to link into a single methodological block the entire system of scientific-methodological and organizational-methodological support of training areas at the Institute, and not just individual disciplines, to significantly improve the quality of bachelor's and master's training on this basis. The educational and methodological work provides for improving the quality of methodological training of the teaching staff, the development of thematic plans, methodological manuals and other methodological materials. The university should carry out systematic work on methodological support not only for individual academic disciplines, but also for educational processes that ensure the preparation of bachelor's and master's degrees.
Keywords: методическая работа; формы методической работы; textbooks; Methodical work; методические разработки; план работы кафедр; создание учебных пособий; the work plan of the departments; the main forms of methodological work; scientific research on the methodology of teaching and educating students; methodological developments; the creation of textbooks; instructional and methodological classes; methodological support for demonstration open and trial classes; mutual attendance of classes; participation in scientific and methodological conferences and interdepartmental meetings; methodological seminars; improvement of the structure and content of academic disciplines; discipline programs; methods of conducting training sessions; improvement of methodological skills of teachers; results of monitoring and mutual attendance of classes; exchange of experience of teachers; ways to improve the quality of teaching and education of students; методики обучения студентов; методики воспитания студентов